Developing of Teaching Materials in Inclusive Education Settings to Improve Critical Thinking Skills of Students with Special Needs - Nuril Nuzulia; Abd. Gafur; Rikza Azharona (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2021)
This research is motivated by the fact that some students with special needs in these schools have difficulty working on hots-based questions, at that school there is also no teaching materials specifically for children with special needs who attend regular schools, so that students experience learning difficulties because the teaching materials are not suitable. with the characteristics of students with special needs. The objectives of this study include: 1) Describing the validity of teaching materials in inclusive education settings, 2) Describing the increase in critical thinking skills of students with special needs between before and after using teaching materials, 3) Describing the responses of students with special needs to teaching materials in inclusive education settings. Research and development uses a model adapted by Borg and Gall. Of the ten development steps, the researcher only applies seven development. steps. The results of this development indicate 1) the module specification consists of cover, author words, table of contents, material, evaluation questions, and author's bio. The results of the research were 82% content experts with good qualifications, 86% learning media experts with good qualifications, 82% learning experts with good qualifications. 2) The results of the attractiveness of teaching materials, the researcher conducted a post test in the experimental class to 4 students with a percentage achievement of 82% with good qualifications. This shows that the use of teaching materials has reached attractive and valid criteria. Analysis of the data used by the Independent Samples T-Test with the SPSS 16 tool and the Sig 0.048 0.05, then Ho was rejected, meaning that there was a difference in learning outcomes from students who had used teaching materials. So it can be concluded that the use of teaching materials in an inclusive education setting can improve the critical thinking skills of students with special needs.